Website Database Development for Radyakartiyasa using the Directus Headless CMS - Irdina, Mutiara; Luthfi, Ahmad (Sistemasi: Jurnal Sistem Informasi, 2025)
Kawadenan Radyakartiyasa, under the auspices of the Karaton Ngayogyakarta Hadiningrat, plays a vital role in cultural preservation and the management of historical tourism destinations. To broaden the reach of information and enhance the promotion of cultural events and Kagungan Dalem heritage sites, a website database was developed as the core foundation of the digital information system. The development process adopted the Agile methodology with the Scrum framework, involving sprint planning to prioritize collections, daily scrums to synchronize progress, sprint reviews to evaluate outcomes, and sprint retrospectives to improve processes. The system was built using the Directus Headless CMS, which decouples the backend and frontend, enabling non-technical teams to manage content efficiently while supporting cross-platform integration. The resulting system includes core collections such as Navigation, Destination Index, Event Index, Hero Banner, FAQ, and other supporting collections, all designed to systematically accommodate information and support multilingual display. These features significantly improve content management efficiency by accelerating information updates, reducing data redundancy, and simplifying content organization in multiple languages. Inter-collection integration ensures consistent information across all website pages, enabling users to quickly and systematically access the data they need. Collection endpoint testing was conducted using Postman to verify that all functions operate according to design specifications and support more organized content management.